Potential for delayed improvement of left ventricular ejection fraction in newly diagnosed heart failure under optimized therapy depends on etiology - data from the PROLONG-II study. (19th May 2022) - Mueller-Leisse, J; Brunn, J; Zormpas, C; Hohmann, S; Hillmann, HAK; Eiringhaus, J; Bauersachs, J; Veltmann, C; Duncker, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients with a first diagnosis of heart failure with reduced ejection (HFrEF) have potential for improvement under appropriate therapy. We and others have previously suggested to extend the time of therapy optimization beyond 3 months before considering implantation of a primary preventive implantable cardioverter-defibrillator (ICD), in order to avoid unnecessary ICD implantations. This sub-analysis of the PROLONG-II study sought to investigate which patients show recovery of left ventricular ejection fraction (LVEF) beyond 3 months under optimized therapy. Methods: Patients with newly diagnosed HFrEF with either ischemic cardiomyopathy (ICM), dilated cardiomyopathy (DCM), peripartum cardiomyopathy (PPCM) or myocarditis at our center between 2012 and 2017 were included. All patients received a wearable cardioverter defibrillator (WCD) for temporary protection from sudden cardiac death. Follow-up (FU) data were analyzed after 3 months and at last available FU, and included WCD data, clinical status, medication, echocardiography and ECG. Results: 353 patients (69% male) with newly diagnosed HFrEF (LVEF 25±8%) were followed for 2.8±1.5 years: 126 patients with ICM (35%), 169 patients with DCM (48%), 27 patients with PPCM (7%), 24 patients with myocarditis (7%) and 7 patients with other diagnoses (2%). LVEF improvement within the first 3 months was observed in all subgroups but was more pronounced in patients with DCM (9±9%) compared to ICM (5±8%) and in PPCM (20±10%) and myocarditis (15±9%) compared to both DCM and ICM. In patients with DCM and PPCM, LVEF continued to improve significantly beyond 3 months (another 10% each). Conclusion: Potential for delayed LVEF improvement in newly diagnosed HFrEF under optimized therapy depends on etiology. Patients with PPCM and DCM seem to be particularly eligible for an extended period of therapy optimization and risk stratification before considering an ICD.